FENOMENA KASUS PERCERAIAN PADA USIA PERNIKAHAN DI BAWAH 5 (LIMA) TAHUN DI ERA POSTMODERNISNME (Studi di Pengadilan Agama Semarang) - Dian Rosita; Naili Azizah (Universitas Karya Husada Semarang, 2023)
Divorce cases is increasing and become a trend for the last three years in Indonesia. Divorce is much more socially acceptable in today's society. The hedonic, consumptive, informative and imaginary characteristics of a post-modernist society are indicators of factors that cause divorce.This study using a normative legal research method with a statutory and analytical approach. The purpose is to find out how the view of marriage in the postmodern era, factors that cause divorce at the age of marriage under five years, and the considerations of the Religious Courts judges decided the case referring to SEMA No. 1 Year 2022. The results state that the personal character in the postmodern era can be an illustration of how they view many things, especially about marriage. Couples who decide on marriage should have mental preparation, economy, and education first. Compromise also an understanding of lifestyle and behavior between partners also need to be discussed before and after marriage so the age of marriage does not stop when still under five years but can continue into old age together.